2018
DOI: 10.1186/s12882-018-1060-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C-induced oxalate nephropathy in a renal transplant patient related to excessive ingestion of cashew pseudofruit (Anacardium occidentale L.): a case report

Abstract: BackgroundIngestion of vitamin C is generally regarded as harmless. Oxalate nephropathy is an infrequent condition and is characterized by oxalate deposition in the renal tubules, in some cases resulting in acute kidney injury. It can be caused by overproduction of oxalate in genetic disorders and, more frequently, as a secondary phenomenon provoked by ingestion of oxalate or substances that can be transformed into oxalate in the patient.Case presentationWe present a case of acute oxalate nephropathy in a 59-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In some patients this process can be accelerated with dramatic clearance of plasma oxalate up to a year after transplantation, leading to delayed graft function and potentially poor long-term graft survival [5, 6]. Cases of oxalate nephropathy causing impaired renal function have also been described many years after renal transplantation in the setting of excessive dietary oxalate intake, including high doses of vitamin C [7, 8]. The presence of preexisting chronic allograft dysfunction can act as an additional risk factor for hyperoxaluria in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients this process can be accelerated with dramatic clearance of plasma oxalate up to a year after transplantation, leading to delayed graft function and potentially poor long-term graft survival [5, 6]. Cases of oxalate nephropathy causing impaired renal function have also been described many years after renal transplantation in the setting of excessive dietary oxalate intake, including high doses of vitamin C [7, 8]. The presence of preexisting chronic allograft dysfunction can act as an additional risk factor for hyperoxaluria in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have demonstrated that regular use of CAM preparations that share the same metabolic cytochrome (CY) P450 pathways as commonly prescribed calcineurin inhibitors (CNI) can cause significant drug level variability and have been linked to acute rejection and risk of graft loss. 9 Other preparations conversely might lead to high levels and subsequent drug toxicity, 10 or may be directly nephrotoxic [11][12][13][14] (Table 1).…”
mentioning
confidence: 99%
“…1 AKI has been described in various settings: ingestion of self-prescribed food supplements or vitamin C-rich fruit (e.g., cashew pseudofruit) and intravenous administration for its antioxidant properties in intensive care (e.g., septic shock or burn patients) or in alternative medicine clinics. [1][2][3] The amount of ingested vitamin C required to induce AKI is unknown. The dose and duration of intake vary widely in the reported literature, ranging from 480 mg to 60 g/d taken from between 1 day to several years, respectively.…”
mentioning
confidence: 99%
“…3 Reported cases include patients presenting with either an underlying kidney disease (e.g., chronic kidney disease due to diabetic nephropathy, obstructive AKI, or kidney transplant recipients) or another predisposing condition for hyperoxaluria such as enteric hyperoxaluria. [1][2][3] Treatment comprises of vitamin discontinuation and supportive care. Hemodialysis may be necessary while awaiting potential renal recovery and treatment of underlying predisposing disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation